2008
DOI: 10.1007/s00213-008-1300-y
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant activity of curcumin: involvement of serotonin and dopamine system

Abstract: The study provides evidences for mechanism-based antidepressant actions of curcumin. The coadministration of curcumin along with piperine may prove to be a useful and potent natural antidepressant approach in the management of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
220
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(230 citation statements)
references
References 26 publications
(29 reference statements)
5
220
0
5
Order By: Relevance
“…Both extract used are extensively studied as herbal medicines in the treatment of depression and stress-induced disorders. 14,15,[17][18][19][20]24 The novelty of the study is the evaluation of their effi cacy in combination and testing possible synergic effects. In addition, data on the effect of these two plants on LPS-induced immunoreactivity in CMS was obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both extract used are extensively studied as herbal medicines in the treatment of depression and stress-induced disorders. 14,15,[17][18][19][20]24 The novelty of the study is the evaluation of their effi cacy in combination and testing possible synergic effects. In addition, data on the effect of these two plants on LPS-induced immunoreactivity in CMS was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that Curcuma extract leads to decrease in the level of TNF-α based on the regulation of the abnormalities in the HPA-axis as well as its antiinfl ammatory properties -acting as COX-2 and NF-kB inhibitor. [18][19][20]31 The infl uence of Rhodiola on the TNF-α levels could be explained with its strong antioxidant potential and anti-infl ammatory effect. Lee et al in their study observed decrease in the TNF-α levels after LPS challenge in mice treated orally with Rhodiola 500 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, curcumin is a potent antioxidant that can lower markers of oxidative stress (Naik et al, 2011, Rai et al, 2010, modulate immuno-inflammation by acting as a COX-2 inhibitor (Lee et al, 2011, Plummer et al, 1999 and lower pro-inflammatory cytokines (Basnet andSkalko-Basnet, 2011, Belcaro et al, 2010), provide significant neuroprotection , Xu et al, 2007, modulate HPA activity , Li et al, 2009) and influence monoamine transmission through its effect on serotonergic and dopaminergic activity (Bhutani et al, 2009, Kulkarni et al, 2008, Xia et al, 2007. In animal studies, antidepressant effects of curcumin have been attributed to its serotonergic, dopaminergic, neuroprotective and HPA-modulating effects , Kulkarni et al, 2008, Xu et al, 2006. Two clinical trials have also now been completed investigating the antidepressant effects of curcumin in people with major depression.…”
Section: Introductionmentioning
confidence: 99%
“…Forced swim test are quite sensitive and widely employed in rodents to predict antidepressant potential by reduction of immobility period [27]. It is reported that haloperidol induced depression in forced swim test [3].…”
Section: Discussionmentioning
confidence: 99%